Polygenic risk for schizophrenia and neurocognitive performance in patients with schizophrenia. (8th August 2017) - Wang, S.‐H.; Hsiao, P.‐C.; Yeh, L.‐L.; Liu, C.‐M.; Liu, C.‐C.; Hwang, T.‐J.; Hsieh, M. H.; Chien, Y.‐L.; Lin, Y.‐T.; Chandler, S. D.; Faraone, S. V.; Laird, N.; et al.
Abstract : Both neurocognitive deficits and schizophrenia are highly heritable. Genetic overlap between neurocognitive deficits and schizophrenia has been observed in both the general population and in the clinical samples. This study aimed to examine if the polygenic architecture of susceptibility to schizophrenia modified neurocognitive performance in schizophrenia patients. Schizophrenia polygenic risk scores (PRSs) were first derived from the Psychiatric Genomics Consortium (PGC) on schizophrenia, and then the scores were calculated in our independent sample of 1130 schizophrenia trios, who had PsychChip data and were part of the Schizophrenia Families from Taiwan project. Pseudocontrols generated from the nontransmitted parental alleles of the parents in these trios were compared with alleles in schizophrenia patients in assessing the replicability of PGC‐derived susceptibility variants. Schizophrenia PRS at the P ‐value threshold (PT) of 0.1 explained 0.2% in the variance of disease status in this Han‐Taiwanese samples, and the score itself had a P ‐value 0.05 for the association test with the disorder. Each patient underwent neurocognitive evaluation on sustained attention using the continuous performance test and executive function using the Wisconsin Card Sorting Test. We applied a structural equation model to construct the neurocognitive latent variable estimated from multiple measured indices in these 2 tests, and then tested the association between the PRS and the neurocognitive latent variable. Higher schizophrenia PRS generated at the PT of 0.1 was significantly associated with poorer neurocognitive performance with explained variance 0.5%. Our findings indicated that schizophrenia susceptibility variants modify the neurocognitive performance in schizophrenia patients. Abstract : Schizophrenia PRS at threshold 0.1 was associated with poorer neurocognitive performance ( R 2 = 0.5%).